Deforestation homogenizes tropical parasitoid-host networks - Laliberté, Etienne; Tylianakis, Jason M (Ecology (Durham), 2010)
Human activities drive biotic homogenization (loss of regional diversity) of many taxa. However, whether species interaction networks (e.g., food webs) can also become homogenized remains largely unexplored. Using 48 quantitative parasitoid-host networks replicated through space and time across five tropical habitats, we show that deforestation greatly homogenized network structure at a regional level, such that interaction composition became more similar across rice and pasture sites compared with forested habitats. This was not simply caused by altered consumer and resource community composition, but was associated with altered consumer foraging success, such that parasitoids were more likely to locate their hosts in deforested habitats. Furthermore, deforestation indirectly homogenized networks in time through altered mean consumer and prey body size, which decreased in deforested habitats. Similar patterns were obtained with binary networks, suggesting that interaction (link) presence-absence data may be sufficient to detect network homogenization effects. Our results show that tropical agroforestry systems can support regionally diverse parasitoid-host networks, but that removal of canopy cover greatly homogenizes the structure of these networks in space, and to a lesser degree in time. Spatiotemporal homogenization of interaction networks may alter coevolutionary outcomes and reduce ecological resilience at regional scales, but may not necessarily be predictable from community changes observed within individual trophic levels.